2020
DOI: 10.3390/jfmk5020037
|View full text |Cite
|
Sign up to set email alerts
|

Energetic and Biomechanical Contributions for Longitudinal Performance in Master Swimmers

Abstract: Background: The current study aimed to verify the changes in performance, physiological and biomechanical variables throughout a season in master swimmers. Methods: Twenty-three master swimmers (34.9 ± 7.4 years) were assessed three times during a season (December: M1, March: M2, June: M3), in indoor 25 m swimming pools. An incremental 5 × 200 m test was used to evaluate the speed at 4 mmol·L−1 of blood lactate concentration (sLT), maximal oxygen uptake (VO2max), peak blood lactate ([La-]peak) after the test, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Previous studies that focused on the training effect in master swimmers found improvements in energetic variables (e.g., oxygen uptake [ 30 ]), biomechanical indicators (e.g., stroke length and frequency, and propelling efficiency [ 4 , 6 , 7 ]), and race performance [ 30 , 31 ]. Past research also indicated that in this specific age group, performance throughout the season seems to be more dependent on technical factors [ 7 ], meaning that active drag reduction due to technical improvements would result in performance optimization. In fact, the observed performance enhancement identified in the present study was probably due to the active drag reduction, with swimmers reducing the power needed to propel through the water along the training mesocycle.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies that focused on the training effect in master swimmers found improvements in energetic variables (e.g., oxygen uptake [ 30 ]), biomechanical indicators (e.g., stroke length and frequency, and propelling efficiency [ 4 , 6 , 7 ]), and race performance [ 30 , 31 ]. Past research also indicated that in this specific age group, performance throughout the season seems to be more dependent on technical factors [ 7 ], meaning that active drag reduction due to technical improvements would result in performance optimization. In fact, the observed performance enhancement identified in the present study was probably due to the active drag reduction, with swimmers reducing the power needed to propel through the water along the training mesocycle.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings in master swimmers suggested that eight training weeks improved stroke length, stroke index and stroke efficiency [ 7 ], which are efficiency indicators and can be used to evaluate swimming technical changes [ 5 , 10 ]. Moreover, it was identified that front crawl sprint performance (i.e., 15 m, 25 m, 50 m) is dependent on stroke index values in master swimmers of similar age (30–39 years old) to the ones in the current study [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations